LABA ATAU ARUS KAS SEBAGAI PARAMETEK KINERJA PERUSAHAAN BERDASARKAN SIKLUS HIDUP PERUSAHAAN - Riza Lailatul Qodriyah (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2012)
This research is aimed to know earning or cash flow has value relevance with use life cycle of firm. Life cycle of firm is distinguished to four stage. They are start up stage, growth stage, maturity stage and decline stage. Cash flow are predicted to be used accounting measure in start up, growth and decline stage and than in maturity stage, earning are expected to be more value relevance as accounting measure. This research use manufacture industries in Indonesian as sample of the research. The samples have classified by Indonesian Capital Market Directory in 2008. There 128 firms are used sample in this research and with three years research, 2005-2007. And then the firms are classified to life cycle of firm with cash flow patterens metode. The result of this research can show that earning can use accouting measure in start up stage and cash flow can use accouting measure in growth stage. Accounting measure for the maturity stage is earning and cash flow. But in this research can not examine firms in decline stage because the firms sample in decline stage just six firms and three years research.